DETERMINATION OF HUMAN AGE BY MORPHOLOGICAL CHARACTERISTICS OF THE STERNUM - Akram Z. Otamuradov ,; Mukharrama A. Khasanova,; Ibragim I. Bakhriev , (Central Asian Journal of Medicine, 2024)
During the forensic examination of the corpses of unknown persons for the purpose of identification, as well as in the conditions of strongly developed decay changes in the corpses or during their criminal dissection, the study of the bones of the human skeleton can serve to determine the objective evidence of identification process. Currently, the forensic identification of unknown corpses issues of medicine and expertise remain important, as the number of armed conflicts, terrorist attacks, natural disasters, man-made disasters, and criminal murders remains high. With expertise and investigations carried out in this department, rapid search in the course of conducting criminal and civil cases and solving many issues that arise before the prosecutor's office, the examination of the identity of the person is important for the determination of justice.